2021
DOI: 10.1111/ene.14839
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy for wake‐up stroke: A systematic review and meta‐analysis

Abstract: Background and purpose According to evidence‐based clinical practice guidelines, patients presenting with disabling stroke symptoms should be treated with intravenous tissue plasminogen activator (IV tPA) within 4.5 h of time last known well. However, 25% of strokes are detected upon awakening (i.e., wake‐up stroke [WUS]), which renders patients ineligible for IV tPA administered via time‐based treatment algorithms, because it is impossible to establish a reliable time of symptom onset. We performed a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Our trial adds evidence to a previous systematic review and meta-analysis of controlled trials, observational cohort studies and single-arm safety studies which showed no significant difference in functional or safety outcomes between studies that evaluated patients with non-contrast CT, MRI, or CT perfusion prior to treatment. 30 Our trial has several limitations. Based on a revised power estimation, the recruitment target was increased from 500 to 600 patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our trial adds evidence to a previous systematic review and meta-analysis of controlled trials, observational cohort studies and single-arm safety studies which showed no significant difference in functional or safety outcomes between studies that evaluated patients with non-contrast CT, MRI, or CT perfusion prior to treatment. 30 Our trial has several limitations. Based on a revised power estimation, the recruitment target was increased from 500 to 600 patients.…”
Section: Discussionmentioning
confidence: 95%
“…Denmark: National Coordinator H.K. Christensen Bispebjerg Hospital (30), L. Christensen (PI), K. AEgidius (PI), H.K. Christensen, T. Pihl, C. Fassel-Larsen, A. Hansen, N. Preisler, M. Folke, L. Wassvik.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…(WUS is defined here as the scenario where a person wakes up with symptoms of stroke having gone to bed previously symptom free, and where their last known well time >4.5 hours prior 12 ).…”
Section: Quantitative Inclusion Criteriamentioning
confidence: 99%
“…En presencia de un ictus isquemico agudo la evidencia actual avala el tratamiento con activador tisular del plasminógeno intravenoso (alteplasa), dentro de las 4,5 horas del inicio de los sintomas (8).…”
Section: Introductionunclassified